Islamic regulations of woman's work outside home - Abdul Karim, Asar; Ghalia, Bouhedda; Jusoh, N. Marniwati (2014)
The issue of woman's work outside in Islam, is a topic of great misunderstanding and distortion due partly to the lack of understanding, partly due to misbehavior of some Muslims, but also mainly to the disagreement between Muslim scholars. After comparing those arguments made by the Muslim scholars, the researcher found that there is no absolute restriction in Islamic law that says a woman cannot work nor have a profession, which her main place is in the home. In fact, a truly Islamic society must be comprised of women who work as physicians, nurses, teachers since it's preferable to separate teenagers in the volatile years in the high school education. this paper proposes a solution to overcome such problem by discussing the Islamic regulations for women who work outside their home. This is the main gap that exists between the Muslim scholars in their arguments, whereby their main concern is still in the traditional way, i.e by interpreting Shari'ah texts based on their respective preference/understanding. By the detailed discussion about the Islamic regulations which comprised of guidelines/conditions of woman's work outside, the disagreement among the Muslim scholars seems to be eliminated, or at least it can be reduced to a minimum level.